Manajemen Kurikulum Pembelajaran Bahasa Arab di Madrasah Aliyah - Nurul Fika; Salimah Salimah; Eneng Siti Suherni; Atiqoh Atiqoh; Nasiruddin Nasiruddin; Yuyun R. Uyuni (Journal on Education, 2023)
This research uses a type of qualitative research with a library research approach by exploring information through literature related to the management of the Arabic language learning curriculum in madrasah aliyah and to answer the focus of the study in this research. This study examines the definition of Arabic curriculum management, the implementation of Arabic language learning, the steps of Arabic language learning. Curriculum is one of the important things that must exist in an educational institution.